Vascular Lesions, APOE ε4, and Tau Pathology in Alzheimer Disease. Issue 3 (22nd February 2021) - Nichols, Jodie B; Malek-Ahmadi, Michael; Tariot, Pierre N; Serrano, Geidy E; Sue, Lucia I; Beach, Thomas G
Abstract: We sought to determine the associations among cerebral amyloid angiopathy (CAA), white matter rarefaction (WMR), circle of Willis atherosclerosis (CWA), and total microinfarct number with Braak neurofibrillary stage in postmortem individuals with and without Alzheimer disease (AD). Data from 355 cases of autopsied individuals with Braak stage I–VI who had antemortem consensus diagnoses of cognitively unimpaired (n = 183), amnestic mild cognitive impairment (n = 31), and AD dementia (n = 141) were used. The association between Braak stage and vascular lesions were individually assessed using multivariable linear regression that adjusted for age at death, APOE ε4 carrier status, sex, education, and neuritic plaque density. CAA (p = 0.007) and WMR (p < 0.001) were associated with Braak stage, independent of amyloid load; microinfarct number and CWA showed no association. Analyses of the interactions between APOE ε4 carrier status and vascular lesions found that greater WMR and positive ε4 carrier status were associated with higher Braak stages. These results suggest that CAA and WMR are statistically linked to the severity of AD-related NFT pathology. The statistical link between WMR and NFT load may be strengthened by the presence of APOE ε4 carrier status. An additional finding was that Lewy body pathology was most prevalent in higher Braak stages.